The Influence of Brand Image And Price Perception on Consumer Purchase Decisions on Buttonscarves in East Java - Elfina Nur Hidayati; Siti Aminah (Indonesian Journal of Business Analytics, 2023)
This study aims to evaluate the impact of brand image and price perceptions on purchasing decisions for Buttonscarves headscarves. The method applied in this study is a quantitative approach using a purposive sampling technique. The research sample consisted of 100 consumers who had purchased Buttonscarves Veils in the East Java region. Data for this study were collected by filling out questionnaires which were distributed to these consumers. Data analysis was performed using the Partial Least Square (PLS) model. The findings of this study indicate that brand image and price perceptions have a significant influence on the purchasing decisions of consumers who buy Buttonscarves Veils in East Java.